State Emergency Service Volunteer views on expectations, experiences, and motivations: Findings from the Cultural Assessment Tool survey - Farid, H.; Kragt, Darja; Dunlop, Patrick; Gagné, Marylène; Luksyte, A.; Holtrop, Djurre (Bushfire and Natural Hazards CRC, 2019)
In 2018, The University of Western Australia and the Department of Fire and Emergency Services (DFES) collaborated to obtain more information on the current state of volunteering in Western Australia (WA), specifically on volunteer recruitment, retention, wellbeing, and diversity within the State Emergency Service (SES). The key survey information and findings are presented below: